PENCEGAHAN PERNIKAHAN ANAK UNTUK MEWUJUDKAN KELUARGA MAṢLAḤAH PERSPEKTIF BADRIYAH FAYU - Hikmiyah, Hawa' Hidayatul (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2024)
This article is about preventing child marriage to create a maslahah family in Badriyah Fayumi's view. Early childhood marriage has many negative impacts, especially for girls. At an immature age, quarrels will often occur and this often leads to violence, both physical and verbal. This research uses a literature study approach. The research context is analyzed using legislation (juridical). The data used are books about child marriage and maslahah families. The research results show that Badriyah uses a ma'ruf approach. According to her, child marriage poses a threat to the realization of children's basic rights.. Apart from having a physical and psychological impact on children, marriage at a young age increases poverty rates, school dropouts, stunting, and increases the risk of cervical cancer. According to Badriyah Fayumi, child marriage cannot achieve a harmonious family, and can weaken offspring and future generations. Weak ability, mind and reproductive organs.